(3GdedNU GdhGaj HGdEjVGM hGdJHjGfs - (3YHO GddWja Hf Ydis; (3YHO GddWja Hf Ydjs ((3CMeO Hf jhSa s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg Pi Gdef hGdEMSGf CeG HYO ajbhd GdYHO GdabjQ Edi Gddg GdZfi YHO GddWja Hf Ydi hSejJ GdeJf GdedNU GdcGai ai Ydei GdeYGfi hGdHjGf hGdTQM GdedNU GdhGai HGdEjVGM hGdJHjGf s
(3BNQgG (B:s
(3gPG BNQ eG ChQOfG LeYg ef GdahGFO hfXeg ef GdaQGFO eY JhGJQ MhGOK ChQKJ GdWHY edGdkG hGdNGWQ cdGdkG hGdMeO ddg Ydi GdJeGe hYdi fHjg eMeO GdUdGI hGdSdGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdHdGZIs